Th2 cytokine bias induced by silver nanoparticles in peripheral blood mononuclear cells of common bottlenose dolphins (Tursiops truncatus) - Wen-Ta Li; Lei-Ya Wang; Hui-Wen Chang; Wei-Cheng Yang; Chieh Lo; Victor Fei Pang; Meng-Hsien Chen; Chian-Ren Jeng (PeerJ, 2018)
Background Silver nanoparticles (AgNPs) have been widely used in many commercial products due to their excellent antibacterial ability. The AgNPs are released into the environment, gradually accumulate in the ocean, and may affect animals at high trophic levels, such as cetaceans and humans, via the food chain. Hence, the negative health impacts caused by AgNPs in cetaceans are of concern. Cytokines play a major role in the modulation of immune system and can be classified into two types: Th1 and Th2. Th1/Th2 balance can be evaluated by the ratios of their polarizing cytokines (i.e., interferon [IFN]-γ/Interleukin [IL]-4), and animals with imbalanced Th1/Th2 response may become more susceptible to certain kinds of infection. Therefore, the present study evaluated the in vitro cytokine responses of cetacean peripheral blood mononuclear cells (cPBMCs) to 20 nm citrate-AgNPs (C-AgNP20) by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). Methods Blood samples were collected from six captive common bottlenose dolphins (Tursiops truncatus). The cPBMCs were isolated and utilized for evaluating the in vitro cytokine responses. The cytokines evaluated included IL-2, IL-4, IL-10, IL-12, interferon (IFN)-γ, and tumor necrosis factor (TNF)-α. The geometric means of two housekeeping genes (HKGs), glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and β2-microglobulin (B2M), of each sample were determined and used to normalize the mRNA expression levels of target genes. Results The ratio of late apoptotic/necrotic cells of cPBMCs significantly increased with or without concanavalin A (ConA) stimulation after 24 h of 10 µg/ml C-AgNP20 treatment. At 4 h of culture, the mRNA expression level of IL-10 was significantly decreased with 1 µg/ml C-AgNP20 treatment. At 24 h of culture with 1 µg/ml C-AgNP20, the mRNA expression levels of all cytokines were significantly decreased, with the exceptions of IL-4 and IL-10. The IFN-γ/IL-4 ratio was significantly decreased at 24 h of culture with 1 µg/ml C-AgNP20 treatment, and the IL-12/IL-4 ratio was significantly decreased at 4 or 24 h of culture with 0.1 or 1 µg/ml C-AgNP20 treatment, respectively. Furthermore, the mRNA expression level of TNF-α was significantly decreased by 1 µg/ml C-AgNP20 after 24 h of culture. Discussion The present study demonstrated that the sublethal dose of C-AgNP20 (≤1 µg/ml) had an inhibitory effect on the cytokine mRNA expression levels of cPBMCs with the evidence of Th2 cytokine bias and significantly decreased the mRNA expression level of TNF-α. Th2 cytokine bias is associated with enhanced immunity against parasites but decreased immunity to intracellular microorganisms. TNF-α is a contributing factor for the inflammatory response against the infection of intracellular pathogens. In summary, our data indicate that C-AgNP20 suppresses the cellular immune response and thereby increases the susceptibility of cetaceans to infection by intracellular microorganisms.